Port Selection Criteria for the Korea-China Train Ferry - Ja-Yeon Lee; Kyong-Jun Yun; Su-Han Woo (International Journal of Supply Chain Management, 2017)
The Korea-China Train Ferry can be one option to enter into Eurasia and a meaningful way to extend the route forlogistics enterprise and manufacturers of Korea to reach the broaderglobal marketalong with specific access to China. Under this scenaris, this study is designed to look at the progress and status of the Korea-China Train Ferry project as anopportunity for Korea to build a path towards Eurasia and to review factors and opinions to consider in port selectionbased on in-depth interviewswith industry participants andexperts. It alsoaims to discuss ideas for a Korea-Chinalogistics cooperative system. For the train ferry's success, agreements between Korea and China are essential to ensure consistency inbase ports and customsclearance procedures and long-term preparation should be made in the first phase to build the framework for the Korea-China Train Ferry operations.